2014
DOI: 10.1109/lpt.2014.2322695
|View full text |Cite
|
Sign up to set email alerts
|

Four-Channel WDM Transmission Over 50-m SI-POF at 14.77 Gb/s Using DMT Modulation

Abstract: Wavelength division multiplexing (WDM) is a promising solution for upgrading the capacity of polymer optical fiber (POF)-based telecommunication networks. In this letter, we report on the successful realization of a four-channel highspeed WDM transmission system for 1-mm diameter step-index POF (SI-POF). For combining the optical signals coming from 405-, 450-, 515-, and 639-nm laser diodes onto 1-mm SI-POF, a 4 × 1 coupler with low insertion loss (IL) has been developed. To spatially separate different wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…This value includes the IL produced by two polished surfaces. IL uniformity in a 5 channel configuration is 1.3 dB, more than 1dB below the 4 channel configuration reported in [6] and it is reduced below 0.9 dB in a 4 channel configuration. It is also shown that the spectral bandwidth at -25 dB is higher than 38 nm.…”
Section: Multiplexer and Demultiplexermentioning
confidence: 54%
See 2 more Smart Citations
“…This value includes the IL produced by two polished surfaces. IL uniformity in a 5 channel configuration is 1.3 dB, more than 1dB below the 4 channel configuration reported in [6] and it is reduced below 0.9 dB in a 4 channel configuration. It is also shown that the spectral bandwidth at -25 dB is higher than 38 nm.…”
Section: Multiplexer and Demultiplexermentioning
confidence: 54%
“…A CWDM configuration with 4 channels is going to be considered for comparison purposes with the solution reported in [6]. For the worst case channel, a power budget improvement of 3.6 dB is achieved (2.1 dB in the DEMUX IL and 1.5dB in the MUX IL), see Table I, in an overall power budget of 18dB.…”
Section: Power Consumption Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These advantages will provide a broad tuning range either straining or heating the fiber, and easy handling due to its low stiffness and therefore, lower installations cost. However, the product of bandwidth and channel length is somewhat reduced due to higher loss [13] and they are suitable for in-building and short range applications.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a new wavelength optical carrier can be added to a WDM system if new optical sources and filters are developed. Many WDM techniques can have been reported in the literature recently [9][10][11][12]. However, none of them explore the yellow/orange transmission window (560-600 nm) because semiconductors compounds such as GaAsP, AlGaInP and GaP:N are not interesting materials allowing to develop fast, efficient and fiber-integrable sources at such window [7].…”
mentioning
confidence: 99%